Genome-wide association identifies a deletion in the 3’ untranslated region of Striatin in a canine model of arrhythmogenic right ventricular cardiomyopathy: Identification of Striatin deletion in canine ARVC - Meurs, Kathryn M. (2010)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a familial cardiac disease characterized by ventricular arrhythmias and sudden cardiac death. It is most frequently inherited as an autosomal dominant trait with incomplete and age-related penetrance and variable clinical expression. The human disease is most commonly associated with a causative mutation in one of several genes encoding desmosomal proteins. We have previously described a spontaneous canine model of ARVC in the boxer dog. We phenotyped adult boxer dogs for ARVC by performing physical examination, echocardiogram and ambulatory electrocardiogram. Genome-wide association using the canine 50k SNP array identified several regions of association, of which the strongest resided on chromosome 17. Fine-mapping and direct DNA sequencing identified an eight base pair deletion in the 3’ untranslated region (UTR) of the striatin (STRN) gene on chromosome 17 in association with ARVC in the boxer dog. Evaluation of the secondary structure of the 3’ UTR demonstrated that the deletion affects a stem loop structure of the mRNA and expression analysis identified a reduction in striatin mRNA. Dogs that were homozygous for the deletion had a more severe form of disease based on a significantly higher number of ventricular premature complexes. Immunofluorescence studies localized striatin to the intercalated disc region of the cardiac myocyte and co-localized it to three desmosomal proteins, plakophilin- 2, plakoglobin and desmoplakin, all involved in the pathogenesis of ARVC in human beings. We suggest that striatin may serve as a novel candidate gene for human ARVC.